Ecomat 14: Conventional Lathe : Introduction Manual Emcomat 14 (Ref.-no.EN 2203 - Edition B2011-09) - EMCO group (EMCO group, 2011)
For more than five decades EMCO has been developing and building wood and working machine and has been successfully on the market since 1980 with computer controled machine tools. The high degree of experience is an advantage for the EMCOMAT lathe model series. The machine can be operated simply and due to most recent machining techniques according to ISO 9001:2000. For later operators with CNC experience as well as preliminary step for CNC technology the EMCOMAT 14 lathes are particulary adequate. The are provided with a digiral path - measuring system wich offers the possibility of tool and workpiece contour storage. Due to the worldwide industrial use of our machines we dispose of a service network wich covers all world areas. In the present operating instructions you will find a complete description of safety hints, transport, set - up, operation and maintenance of the machine.